Consequences of Making the Inactive Active Through Changes in Antisense Oligonucleotide Chemistries - Zaw, Khine; Greer, Kane; Aung-Htut, May Thandar; Mitrpant, Chalermchai; Veedu, Rakesh N.; Fletcher, Sue; Wilton, Steve D. (Frontiers in Genetics, 2019)
Antisense oligonucleotides are short, single-stranded nucleic acid analogues that can interfere with pre-mRNA processing and induce excision of a targeted exon from the mature transcript. When developing a panel of antisense oligonucleotides to skip every dystrophin exon, we found great variation in splice switching efficiencies, with some antisense oligonucleotides ineffective, even when directed to canonical splice sites and transfected into cells at high concentrations. In this study, we re-evaluated some of these ineffective antisense oligonucleotides after incorporation of locked nucleic acid residues to increase annealing potential. Antisense oligonucleotides targeting exons 16, 23 and 51 of human DMD transcripts were synthesized as two different chemistries; 2′-O-methyl modified bases on a phosphorothioate backbone or mixmers of the same chemistry but containing several locked nucleic acid residues, which were then transfected into primary human myotubes, and DMD transcripts were analyzed for exon skipping. The ineffective 2′-O-methyl modified antisense oligonucleotides induced no or weak exon skipping, while all corresponding mixmers did induce readily detectable excision of the targeted exons. Interestingly, the mixmer targeting exon 51 induced two unexpected transcripts arising from partial skipping of exon 51 with retention of 95 or 188 bases from the 5′ region of exon 51. These results indicated that locked nucleic acid/2′-O-methyl mixmers are more effective at inducing exon skipping, however this improvement may come at the cost of activating alternative cryptic splice sites and off-target effects on gene expression.